Preparation of Polymer Nano-composite Materials for Microwave Sensor Application (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, prepared nanocomposite materials made of polyester were prepared with a fixation hardenerratio of 0.1 g per 10 ml of polyester. This percentage was constant in all samples and addition of bothchlorophyll(Cll) and lead oxide (PbO<100nm) as well as lead oxide with chlorophyll by weight percentage(0.2 ,0.5, 0.2 (Cll) with 0.5(PbO)wt.% receptivity, then study coefficient of loss of reflectivity of all sampleswhere the results indicated that most prepared materials correct for use attenuation materials of microwaveswhere is reflection coefficient of all samples larger than (10dB) this show that absorption of compositematerials consistence larger than 90%, then study reflection coefficient and also definition complexpermittivity in the range frequencies (3-5)GHz where observed that value of the complex permittivity largerthan one.